Energy map and effective metric in an effective-one-body theory based on the second-post-Minkowskian approximation - Xiaokai He; Manman Sun; Jiliang Jing; Zhoujian Cao (European Physical Journal C: Particles and Fields, 2021)
Abstract Effective-one-body (EOB) theory was originally proposed based on the post-Newtonian (PN) approximation and plays an important role in the analysis of gravitational wave signals. Recently, the post-Minkowskian (PM) approximation has been applied to the EOB theory. The energy map and the effective metric are the two key building blocks of the EOB theory, and in PN approximation radial action variable correspondence is employed to construct the energy map and the effective metric. In this paper, we employ the PM approximation up to the second order, and use the radial action variable correspondence and the precession angle correspondence to construct the energy map and the effective metric. We find that our results based on the radial action variable correspondence, are exactly the same with those obtained based on the precession angle correspondence. Furthermore, we compare the results obtained in this work to the previous existing ones.